Party political representation in Portugal - Belchior, A. M. (South European Society and Politics, 2008)
This study analyses the degree to which Portuguese parties represent their electorates. In this instance, representation is measured by the degree of congruence between those who vote and those who are elected. The analysis has two dimensions: ideological positioning and attitudes towards democracy. On the first dimension, it appears that, compared to the voters, the parliamentary elite is ideologically more extreme. On the second dimension, one finds that elites are more favourable towards democracy than the electorates they represent.